Development and validation of the Nursing Profession Self‐Efficacy Scale. (12th June 2016) - Caruso, R.; Pittella, F.; Zaghini, F.; Fida, R.; Sili, A.
Abstract : Aim: This study describes the development and validation of the Nursing Profession Self‐Efficacy Scale. Background: Self‐efficacy can be useful in predicting performance, job satisfaction or well‐being. In the nursing field, there is a shortage of studies on self‐efficacy with regard to nurses' global confidence in coping ability across a range of everyday, challenging work situations. Methods: To define the theoretical framework of nursing professional self‐efficacy, two focus groups and a literature review were performed. An empirical study was then conducted to test validity and reliability. Face and content validity, construct validity, concurrent validity, internal consistency and test–retest reliability were examined. The content validity index was evaluated by 12 experts who suggested deleting 11 redundant items. The final developed tool was tested for construct analysis using a cross‐validation approach, randomly splitting the overall sample of 917 nurses in two sub‐groups. Findings: The construct validity indicated two dimensions. The face and content validity were adequate. Test–retest reliability displayed a good stability, and internal consistency (Cronbach's α) was acceptable. Moreover, concurrent validity using the Generalized Self‐Efficacy Scale was in line with the theoretical framework. Conclusion: The scale showed evidence of validity and reliability. The major limitation is the strong influence of the Italian context in the tool development. Implications for nursing and health policy: The Nursing Profession Self‐Efficacy Scale could be a fruitful tool that facilitates the application of theories (i.e. social‐cognitive theory) in the nursing field and even development of interventions. Furthermore, a measurement of self‐efficacy could be used to predict nursing clinical performance.